2023
DOI: 10.1002/chem.202301020
|View full text |Cite
|
Sign up to set email alerts
|

An Amphiphilic Peptide Carrier for HCl Transport

Abstract: Single molecules that co‐transport cations as well as anions across lipid membranes are few despite their high biological utility. The elegant yet simple lipidomimmetic peptide design herein enables efficient HCl transport without the use of any external additives for proton transport. The carboxylic acids in the dipeptide scaffold provide a handle to append two long hydrophobic tails and also provide a polar hydrophilic carboxylate group. The peptide central unit also provides NH sites for anion binding. Prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…11 A time-lapse imaging experiment in the absence of the peptide at pH 7 4. showed no change in emission proving the photostability of TRapH (Fig S13).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…11 A time-lapse imaging experiment in the absence of the peptide at pH 7 4. showed no change in emission proving the photostability of TRapH (Fig S13).…”
mentioning
confidence: 94%
“…Both TRapH and protonated TRapH could be excited at 405 nm (Fig S8) since both species showed some absorption at this wavelength. Before proceeding with the in-cell studies, Since TRapH, showed a ratiometric response between a pH range of 3-6, we next decided to apply a previously established peptide-based synthetic H + ion transporter, Amphiphilic Peptide 1a (Fig S12 ), 11 to HeLa cells to reduce intracellular pH, and record temporal pH changes live (Fig 4). Amphiphilic Peptide 1a, has been reported to reduce pH inside vesicles via transport of H + ions.…”
mentioning
confidence: 99%